3^2(6-2)*(4-6)/3
=(9*4)*(-2/3)
=36*(-2)/3
= -72/3
= -24 (answer)
Answer:
1
= -----------
6(x + 7)
Step-by-step explanation:
3x - 21 x^2 - 49
----------- ÷ -------------
18x - 18 x - 1
3x - 21 x - 1
----------- × -------------
18x - 18 x^2 - 49
Factor the top left:
3x - 21 = 3(x - 7)
Factor the bottom left:
18x - 18 = 18(x - 1)
Factor the new bottom right:
x^2 - 49 = (x + 7)(x - 7)
Multiply and simplify the faction:
3(x - 7) x - 1
----------- × -----------------
18(x - 1) (x + 7)(x - 7)
1
= -------------
6(x + 7)
9514 1404 393
Answer:
d(32) = 28.80
the price Marcus pays on an item with an original price of 32
Step-by-step explanation:
d(32) = 32 -0.1(32)
d(32) = 28.8
The problem statement tells you d(32) is the price Marcus pays when the original price is 32.
Answer:
1) (2,4)
2) (5,-2)
Step-by-step explanation:
those are the points at which the lines cross making them the solutions to the equations